Pandangan, Amalan Dan Cabaran Guru Prasekolah Terhadap Penerapan Kemahiran Berfikir Aras Tinggi Melalui Aktiviti Bermain Dalam Komponen Sains Awal - Rasid, Norhailee Abdul (2022)
The element of Higher Order Thinking Skills (HOTS) has been included in the National Preschool Standard Curriculum (KSPK) Revised 2017, which is after four years of HOTS being transformed in the education system in Malaysia. This study aims to explore the perspectives and identify practices and challenges of preschool teachers on the application of HOTS through play activities in the Early Science component. Based on a qualitative approach of various cases, seven preschool teachers under the Ministry of Education Malaysia (MOE) in the state of Penang were involved in this study. The selection of participants was done using purposive sampling. The data for the study were collected through interviews, observation and document analysis while data analysis was carried out using Atlasti Version-8 software. The findings of the study indicate that all participants have a positive view on the practices of application of HOTS through play activities in the Early Science component. This practice focusing on three main themes namely planning; implementation; and evaluation of teacher teaching and facilitation. It is found that the challenges faced by the participants involved teachers, children, teaching resources and facilitation, classroom environment, student management assistants and parents. Hence, this study suggested the need for the teachers and authorities to collaborate in the implementation of HOTS through play activities, towards producing a generation of thinkers in the future.